Influence of peak gate current and rate of rise of gate current on switching behaviour of SiC MOSFET - Pilli N.K.; Singh S.K. (My University, 2025)
Emergence of SiC technology brought revolutionary reforms in power electronics area. Ability of SiC MOSFETs to operate at high voltage and current ratings makes it a best replacement for Si IGBT. Mere by replacing the Si IGBT with SiC MOSFET will not give the best results, until special care is taken in driving the SiC MOSFET to extract the positives of SiC material. Gate driver for SiC MOSFET should be quick and hard enough to achieve low switching losses. The paper focuses on modelling the SiC MOSFET, taking peak gate current and rate of rise of gate current into consideration. Switching losses are derived in terms of gate current only. The dependency and influence of peak gate current and rate of rise of gate current is validated with experimental results. EMI effects of driving SiC MOSFET is also analysed with the help of experimental results. Understanding the requirement and challenges in driving the SiC MOSFET from peak gate current and rate of rise of gate current is concluded. © 2017 IEEE.